Edukasi Teknologi Pakan Untuk Meningkatkan Produktivitas Ternak Ruminansia Di Desa Pilangrejo, Nglipar, Gunung Kidul, D.I.Yogyakarta - Ajat Sudrajat; Raden Febrianto Christi (Unpad Press, 2023)
Feed technology is one of the best ways to improve the quality and extend the shelf life of feed. Feed consists of forage, legumes, concentrates and others. This service aims to provide knowledge about feed processing and preservation technology for ruminants in Pilangrejo Village, Nglipar, Gunung Kidul D.I.Yogyakarta. This service has been carried out and attended by 25 breeders. Implementation method by providing education and practice directly. The implementation stage begins with the distribution of pre-test questionnaires before the activity, the presentation of material on the introduction of feed technology, the distribution of post-test questionnaires to participants and ends with a question and answer session for participants and speakers. Furthermore, the introduction of feed in the form of forage such as odot grass, elephants, kings, rice straw, field grass and others that can be given with the potential availability in the area, The feed technology education provided is the technology of making feed silage. The results of the service show that knowledge of feed technology has increased at the farmer level based on post tests and direct practice, so it is hoped that with this education the people of Nglipar Village can process animal feed optimally and can be one of the solutions to feed shortages in the dry season.